2017
DOI: 10.1108/wje-12-2016-0149
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of nanosecond pulsed laser ablation of various materials

Abstract: Purpose The purpose of this paper is to analyse nanosecond pulsed laser ablation on both metallic materials and non-metallic materials; a comparison between metallic materials and non-metallic materials has also been included. Design/methodology/approach In this paper, FEM method has been used to calculate the result by means of the finite element method. Furthermore, all the analyses are based on thermal theories. Findings The paper presents a comparison of metallic and non-metallic materials. Besides, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…In order to investigate complex effects as light interacting with BFO thin films, we carried out numerical simulation of transient thermal transport. A commercial software package ANSYS is exploited for the finite element analysis (FEA), which is evident of efficiency and accuracy to deal with the thermal transport problems such as laser annealing [ 27 ] or ablation [ 28 ] for laser‐based processing and thermal‐electric analysis for RF integrated circuits. [ 29 ] Without considering the quantum phenomenon like carrier excitation and relaxation under nonequilibrium condition, reports have indicated that classical Fourier heat transfer could sufficiently describe the lattice's thermal diffusion behavior that take place at the time scale longer than 0.1 ns.…”
Section: Figurementioning
confidence: 99%
“…In order to investigate complex effects as light interacting with BFO thin films, we carried out numerical simulation of transient thermal transport. A commercial software package ANSYS is exploited for the finite element analysis (FEA), which is evident of efficiency and accuracy to deal with the thermal transport problems such as laser annealing [ 27 ] or ablation [ 28 ] for laser‐based processing and thermal‐electric analysis for RF integrated circuits. [ 29 ] Without considering the quantum phenomenon like carrier excitation and relaxation under nonequilibrium condition, reports have indicated that classical Fourier heat transfer could sufficiently describe the lattice's thermal diffusion behavior that take place at the time scale longer than 0.1 ns.…”
Section: Figurementioning
confidence: 99%
“…They found that the height of the microgroove increased with increasing laser power and decreased with scanning speed and repetition rate. Ren et al [10] demonstrated the accuracy of nanosecond laser ablation for general precision machining. Compared with the ultrashort laser ablation, the nanosecond laser ablation is more suitable for general precision machining processes and more efficient for machining efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Ren. J et al [11] suited, the accuracy of nanosecond laser ablation for general precision machining, and Compared to ultrashort laser ablation, nanosecond laser ablation is more efficient and consequently more suitable for general precision machining processes.…”
Section: Introductionmentioning
confidence: 99%